Adventures with the β2-adrenoceptor Receptor: A Career Long Interest in Agonising One of the Most Widely Studied GPCRs - Robin A. Fairhurst (CHIMIA)
Drug discovery is a multi-disciplinary effort in which groups with expertise in a range of areas combine in a unified way to achieve a common goal: to deliver a clinical candidate to evaluate a hypothesis for improving human health. As a medicinal chemist this environment has provided multiple opportunities to be involved in cross-discipline interactions that have been both rewarding and led to outcomes that would not have been possible without an intimate interdisciplinary curiosity. Within this article I aim to share some of my experiences with the β2-adrenoceptor that have fostered such synergistic relationships with several disciplines, but in particular with in vitro pharmacologists looking at different ways to stimulate this G protein-coupled receptor (GPCR). This interest now spans over a quarter of a century and has been intertwined with the delivery of three clinical candidates.